(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Now a days in the competition world powerful artillery is business activities. In our country economic development one of the part business. That business activities supported instruments of digital media. In our country backbone is Rural area. Because of our country is developing through the support of our village development. The digital media give a lots of opportunities to the entrepreneur. The existing marketing method was produce small level of profit at the same time this digital media marketing larger than compare with oldest method. In this paper study about the how to support the digital marketing to rural entrepreneur and Impact of Digital media marketing.